(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2021)
A new species of the actinopterygian fish genus Saurichthys is described on the basis of several specimens from the Sceltrich beds (Meride Limestone Formation) of the UNESCO World Heritage area of Monte San Giorgio. The new species shows among other characters, unsegmented lepidotrichia in all fins and elongated and wide paired fins, suggesting a different adaptation for swimming and catching preys with respect to other Saurichthys species of Monte San Giorgio. Phylogenetic analysis suggests that the new species is closely related to the Saurorhynchus species group. The new finding adds further knowledge to the plasticity and functional adaptations of the genus Saurichthys, which was one of the most successful actinopterygians of the Triassic.